Analisis Curahan Waktu Kerja dalam Pengembangan Beberapa Jenis Komoditi Sayur-Sayuran di Kampung Kehiran Distrik Sentani Timur Kabupaten Jayapura: Analisis Curahan Waktu Kerja dalam Pengembangan Beberapa Jenis Komoditi Sayur-Sayuran di Kampung Kehiran Distrik Sentani Timur Kabupaten Jayapura - La Maga; Anita Rusianti; Lidiah Tereda Iwo; Secilia Vanesa Sepang; Heldo Mariche Waroi; Demas Senik (Journal Science Innovation and Technology (SINTECH), 2026)
Farming is an activity carried out by farmers in managing inputs or production factors in farming. Agricultural inputs will produce agricultural products if transformed with other inputs. Activities to transform production factors require labor in farming. The use of labor in farming will certainly have consequences for farming costs. The purpose of this study was to analyze the amount of work time and labor costs in the development of several types of vegetables in Kehiran Village. The data analysis method was carried out using a quantitative descriptive approach. The results showed that the total amount of work time in vegetable farming was 210.64 HKSP; chili farming was 693.24 HKSP; kale farming was 215.90 HKSP; and red spinach farming was 65.51 HKSP. The total labor cost in cayenne pepper farming was Rp 23,350,000, while in kale farming it was Rp 3,748,571.